(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
This project presents an advanced IoT-based healthcare monitoring system designed to assist diabetic patients in continuous health tracking and early detection of complications. The system integrates wearable sensing devices with urine analysis to monitor multiple physiological and biochemical parameters in real time. This project presents an advanced IoT-based healthcare monitoring system designed to assist diabetic patients in continuous health tracking and early detection of complications. The system integrates wearable sensing devices with urine analysis to monitor multiple physiological and biochemical parameters in real time. This project presents an advanced IoT-based healthcare monitoring system designed to assist diabetic patients in continuous health tracking and early detection of complications. The system integrates wearable sensing devices with urine analysis to monitor multiple physiological and biochemical parameters in real time